ChatGPT Artificial Intelligence Integration in Science Learning Media: Systematic Literature Review - Arie Wahyu Prananta; Nugroho Susanto; Nur Fuadah; Arif Purwantoro (Postgraduate, University of Mataram, 2023)
Artificial Intelligence technology enables organizations to support and improve knowledge management practices. From an AI perspective, knowledge representation defines organizational processes that are familiar with this knowledge. In this era of digitalization, the presence of ChatGPT technology opens opportunities to utilize AI chatbots for education in Indonesia, especially in developing student competencies (skills) needed in the 21st century. Where the purpose of the research is to explain ChatGPT Artificial Intelligence Integration in Science Learning Media. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. We review literature from several publications and analyze the Era of Education 4.0 with the help of computers to improve quality in the industrial sector and also in the field of computer-assisted education. Many innovations can be proposed to improve the quality of learning implementation. GPT chat is a search engine like Google with a form of chat or dialogue. GPT Chat is an information search tool and scientific communication tool. Â Â